Galvanisch vernickelte Kohlenstofffasergewebe zur Herstellung fügefähiger CFK mit Permeationsbarriere. Issue 6 (June 2014) - Böttger‐Hiller, F.; Neumann, S.; Fehrmann, F.; Nier, M.; Böttger, T.; Scharf, I.; Nestler, D.; Böhme, M.; Hahn, S.; Nickel, D.; Wielage, B.; Lampke, T.
<x xml:space="preserve">Abstract</x> Efficient lightweight construction requires intelligent materials that meet versatile functions. One approach to produce functional carbon fiber‐reinforced plastics (CFRPs) is the metallization of carbon fiber fabrics. This results in a crack‐free, homogeneous nickel layer on the fabrics' surfaces. By selecting suitable layer parameters, every single fiber of the entire fabrics will be evenly metallized and allow the application of functional CFRPs as lightweight hydrogen storage.